Using Nectar-Related Traits to Enhance Crop-Pollinator Interactions - Prasifka, Jarrad R.; Mallinger, Rachel E.; Portlas, Zoe M.; Hulke, Brent S.; Fugate, Karen K.; Paradis, Travis; Hampton, Marshall E.; Carter, Clay J. (Frontiers in Plant Science, 2018)
Floral nectar and other rewards facilitate crop pollination, and in so doing, increase the amount and breadth of food available for humans. Though pollinator abundance and diversity (particularly bees) have declined over the past several decades, a concomitant increase in reliance on pollinators presents a challenge to food production. Development of crop varieties with specific nectar or nectar-related traits to attract and retain pollinating insects is an appealing strategy to help address needs of agriculture and pollinators for several reasons. First, many crops have specific traits which have been identified to enhance crop-pollinator interactions. Also, an improved understanding of mechanisms that govern nectar-related traits suggest simplified phenotyping and breeding are possible. Finally, the use of nectar-related traits to enhance crop pollination should be complementary to other measures promoting pollinators, does not limit options for crop production, and does not require any changes by growers other than planting varieties and hybrids that are more attractive or rewarding to pollinators. In this article, we review the rationale for improving crop-pollinator interactions, the effects of specific plant traits on pollinator species, and use cultivated sunflowers as a case study. Recent research in sunflower has (i) associated variation in bee visitation with specific floral traits, (ii) quantified benefits of pollinators to hybrid yields, and (iii) used genetic resources in sunflower and other plants to find markers associated with key floral traits. Forthcoming work to increase pollinator rewards should enable sunflower to act as a model for using nectar-related traits to enhance crop-pollinator interactions.